PARP Inhibitors in Biliary Tract Cancer: A New Kid on the Block? - Ricci, Angela Dalia (Medicines (Basel), 2020)
Poly adenosine diphosphate-ribose polymerase inhibitors (PARPi) represent an effective therapeutic strategy for cancer patients harboring germline and somatic aberrations in DNA damage repair (DDR) genes. BRCA1/2 mutations occur at 1–7% across biliary tract cancers (BTCs), but a broader spectrum of DDR gene alterations is reported in 28.9–63.5% of newly diagnosed BTC patients. The open question is whether alterations in genes that are well established to have a role in DDR could be considered as emerging predictive biomarkers of response to platinum compounds and PARPi. Currently, data regarding PARPi in BTC patients harboring BRCA and DDR mutations are sparse and anecdotal; nevertheless, a variety of clinical trials are testing PARPi as monotherapy or in combination with other anticancer agents. In this review, we provide a comprehensive overview regarding the genetic landscape of DDR pathway deficiency, state of the art and future therapeutic implications of PARPi in BTC, looking at combination strategies with immune-checkpoint inhibitors and other anticancer agents in order to improve survival and quality of life in BTC patients.